Theatre History and the Means of Production: An Analytical Model - McDonald, Larry (Theatre Research in Canada / Recherches théâtrales au Canada, 1989)
This article proposes a critical model for the writing of theatre history that explores the relationship between the way a company is designed to produce theatre and its cultural politics and aesthetic objectives. Until there is a more developed and widespread awareness of the range and importance of different production models, the standard model will go on reproducing itself unself-critically. Cet article propose un modèle critique pour l’élaboration d’une histoire du théâtre qui examinerait les rapports entre, d’une part, la façon dont la production scénique est conçue pour une compagnie theâtrale et, de l’autre, les politiques culturelles et les visées esthétiques de cette compagnie. En attendant qu’on se rende mieux compte des périmètres et de l’importance relative de diffiérents modèles de production, le modèle traditionnel continuera sans doute, selon l’auteur, de se reproduire sans examen critique.